Building the Website of Engino Using a UX Research Approach: An Industry Project - Agathangelou, Lilia (My University, 2023)
Nowadays, more and more businesses recognize the importance of creating websites that are visually appealing, easy to navigate, and provide a positive user experience (UX). This thesis revolves around researching how to build the Engino STEM Center website using UX practices. Starting from an interview to determine the focus of the research, to learn more about similar past efforts from a literature review. The first cycle of work consisted of creating the first low-fidelity wireframes after several interviews and observational visits to the STEM Center. The completion of the first cycle was concluded with an interview which suggested that the website could be more focused on the activities offered by the center. The second cycle started again with an interview and observational visit to the center and continued with the creation of more defined high-fidelity wireframes with limited interactions, such as changing pages, that were presented to several employees of Engino who provided feedback on how to improve them for better viewing by their customers. After incorporating the Engino staff's suggestions, the Adobe XD prototype was updated and then developed into a front-end website using HTML, CSS and Bootstrap libraries. The end phase of this thesis consisted of testing the navigation, aesthetics and impression of the website with 3 end users and 3 semi-relevant users. Once the errors had been identified, the new changes were implemented into the developed website. All changes that were made were aimed to ensure the best user experience that will introduce the website visitor to the company and then help them find what they are looking for or want to discover.
Keywords: user experience; UI/UX; web development; responsive design